Questions of Development of Students’ Functional Literacy - Beisenova, Zhainagul; Kanafiyeva, Kulanda; Moldakhmetova, Saltanat; Kuandykova, Zhanar (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The article is devoted to the definition of critical thinking skills, the stimulation of critical thinking in language teaching. One of the requirements of the global linguistic globalisation is functional literacy, which involves a degree of native languages. Today the objective historical principal is the nomination of more serious requirements to the knowledge level and skills of students. Background: In the current realities, the educational process in higher education institutions should focus on building skills that contribute to the implementation of the concept of “education throughout life”. It is obvious that the main condition for the formation of such skills is the presence of a certain level of functional literacy. Method: To test the hypothesis of the research and achieve the objectives the following methods have been used: theoretical: analysis of pedagogical, philosophical, psychological literature on research; empirical: observation, analysis of results of operations, testing, conducting formative, notes and summarising experiments; statistical: mathematical processing of experimental results. Results: The results of experimental work have shown positive changes in all indicators of the activity component. Significantly reduce the number of students who own conclusions and explanations skills at a low level. Conclusion: To ensure the efficiency of the formation of functional literacy encourage students to apply the technology of critical thinking, which can be used to form the organisational, intellectual and other skills, including the ability to carry out activities of teaching independently.